Peringatan Hari Kemerdekaan Negara Tetangga sebagai Cermin Penguatan Semangat Nasionalisme Indonesia - Rois, Ajun; Permana, Yudi; Herlina, Herlina; Rosidah, Siti; Utami, Siti Fatimah Putri; Hidayati, Nor; Nunung Nasrulloh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The 68th Malaysian Independence Day celebration, carrying the theme “Malaysia Madani: Rakyat Disantuni,” was held on August 28, 2025, at Sekolah Menengah Islam (SMI) Ad-Dimyati, Kuala Selangor, aiming to instill the spirit of patriotism, solidarity, and love for the homeland among the school community. This study employed a descriptive qualitative approach using a case study method through participatory observation, documentation, and thematic analysis. The findings revealed that a series of activities such as classroom decoration competitions, flag-raising ceremonies, poetry recitations, and patriotic song performances effectively strengthened national character values and enhanced the active participation of the entire school community, including teachers, staff, students, and KKN (Community Service Program) students. Beyond a ceremonial celebration, this event served as a means of character education integrated with real-life experiences, aligning with the concept of hidden curriculum in education. These findings emphasize the importance of national day commemorations in educational institutions as a medium for learning historical values, national identity, and social solidarity. Therefore, the Independence Day celebration at SMI Ad-Dimyati can serve as an ideal model for other schools in integrating character education with contextual and reflective national activities.